Well‐Defined Molecular Magnesium Hydride Clusters: Relationship between Size and Hydrogen‐Elimination Temperature. Issue 26 (9th May 2013) - Intemann, Julia; Spielmann, Jan; Sirsch, Peter; Harder, Sjoerd
Abstract A new tetranuclear magnesium hydride cluster, [{NN‐(MgH)2}2], which was based on a NN‐coupled bis‐β‐diketiminate ligand (NN2−), was obtained from the reaction of [{NN‐(MgnBu)2}2] with PhSiH3. Its crystal structure reveals an almost‐tetrahedral arrangement of Mg atoms and two different sets of hydride ions, which give rise to a coupling in the NMR spectrum (J=8.5 Hz). To shed light on the relationship between the cluster size and H2 release, the thermal decomposition of [{NN‐(MgH)2}2] and two closely related systems that were based on similar ligands, that is, an octanuclear magnesium hydride cluster and a dimeric magnesium hydride species, have been investigated in detail. A lowering of the H2‐desorption temperature with decreasing cluster size is observed, in line with previously reported theoretical predictions on (MgH2)n model systems. Deuterium‐labeling studies further demonstrate that the released H2 solely originates from the oxidative coupling of two hydride ligands and not from other hydrogen sources, such as the β‐diketiminate ligands. Analysis of the DFT‐computed electron density in [{NN‐(MgH)2}2] reveals a counterintuitive interaction between two formally closed‐shell H− ligands that are separated by 3.106 Å. This weak interaction could play an important role in H2 desorption. Although the molecular product after H2 release could not be characterized experimentally, DFT calculations on the proposed decomposition product, that is, the low‐valence tetranuclear Mg(I) cluster [(NN‐Mg2)2], predict a structure with two almost‐parallel, localized MgMg bonds. As in a previously reported β‐diketiminate MgI dimer, the MgMg bond is not characterized by a bond critical point, but instead displays a local maximum of electron density midway between the atoms, that is, a non‐nuclear attractor (NNA). Interestingly, both of the NNAs in [(NN‐Mg2)2] are connected through a bond path that suggests that there is bonding between all four MgI atoms.